Aortic Valve Neocuspidalization May Be a Viable Alternative to Ross Operation in Pediatric Patients - Polito, Angelo (Pediatr Cardiol, 2021)
The aim of the study was to evaluate the medium-term results of aortic valve neocuspidalization according to Ozaki compared to Ross procedure for treatment of isolated aortic valve disease in pediatric age. Thirty-eight consecutive patients with congenital or acquired aortic valve disease underwent either Ozaki (n = 22) or Ross (n = 16) operation between 01/2015 and 05/2020. The primary outcome was progression of aortic valve disease and aortic ring and root dimension, whereas secondary outcome was freedom from reintervention or death by type of operation. Median age was 12.4 (8.8–15.8) years and the prevailing lesion was stenosis in 20 cases (52%) and incompetence in 18 (48%). One death occurred in the Ross group in the early postoperative period, while there were no deaths in the Ozaki group. Effective treatment of aortic valve stenosis or regurgitation occurred in both groups and remained stable over a median follow-up of 18.2 (5–32) months. In Ozaki group, 3 patients required aortic valve replacement at 4.9, 3.5, and 33 months, respectively. In Ross group, 1 patient required Melody pulmonary valve replacement, whereas none required aortic valve surgery. Finally, significantly higher aortic transvalvular gradient at follow-up was recorded in Ozaki group compared to Ross group. Overall, there was no significant difference in freedom from reoperation or death between the two groups. The medium-term outcome of Ozaki and Ross in pediatric patients is similar, despite an increased tendency of the former to develop aortic transvalvular gradient in the follow-up. Future larger multicenter studies with longer follow-up are warranted to confirm these results.